Pemanfaatan Limbah Cangkang Telur Menjadi Pupuk Organik - Deswanto Deswanto; Adi Nugroho (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2024)
Egg shell and soil is a combination that can be used to make organic fertilizer. The purpose of this research is to make organic fertilizer from the basic ingredients of egg shells and soil determine its suitability with the fertilizer standard, namely SNI 7763:2018. Fertilizer design begins by determining 4 sample formulations with different ratios between egg shells and soil. The four comparisons of soil and eggshell samples were S1(80%: 20%), S2(50%: 50%), S3(60%: 40%), S4(40%: 60%). The standards and parameters that are used as benchmarks in this research are SNI 7763:2018 and 4 parameters, namely water content, pH, grain size, and co material. Based on the assessment with the SNI standard, only the fourth sample met the SNI standard. Meanwhile, based on the results of statistical tests with the response surface method, it shows that the ratio of soil and egg shells effect the parameters of moisture content, pH, grain size, and co-mingled material.